For this case we must find
![(f + g) (x).](https://tex.z-dn.net/?f=%28f%20%2B%20g%29%20%28x%29.)
By definition we have to:
![(f + g) (x) = f (x) + g (x)](https://tex.z-dn.net/?f=%28f%20%2B%20g%29%20%28x%29%20%3D%20f%20%28x%29%20%2B%20g%20%28x%29)
We have the following functions:
![f (x) = 5x ^ 3-2\\g (x) = 2x + 1](https://tex.z-dn.net/?f=f%20%28x%29%20%3D%205x%20%5E%203-2%5C%5Cg%20%28x%29%20%3D%202x%20%2B%201)
Now, applying the given definition, we have:
![(f + g) (x) = 5x ^ 3-2 + 2x + 1\\(f + g) (x) = 5x ^ 3 + 2x-1](https://tex.z-dn.net/?f=%28f%20%2B%20g%29%20%28x%29%20%3D%205x%20%5E%203-2%20%2B%202x%20%2B%201%5C%5C%28f%20%2B%20g%29%20%28x%29%20%3D%205x%20%5E%203%20%2B%202x-1)
Answer:
![(f + g) (x) = 5x ^ 3 + 2x-1](https://tex.z-dn.net/?f=%28f%20%2B%20g%29%20%28x%29%20%3D%205x%20%5E%203%20%2B%202x-1)
Answer:
30m
Step-by-step explanation:
A=πr²
225π=πr²
225=r²
r=√225
r=15
d=2r
d=2×15
=30m
She is incorrect cause if we take the number 20 and take 25% of it it equals 5 so now 20 is only 15. They if we take 75% away from 20 is equals 15 so then we only have 5 from 20 left. Therefore she’s incorrect because 75% leaves 5/20 and 25% leaves 15/20. Hope that makes sense.
Answer:106.
Step-by-step explanation: